THE PLACE OF UZBEK MUSIC IN THE ART (Archive of Conferences, 2020)
This article discusses the role of makom in the art of Uzbek music, the role of makom art in the education of the younger generation today, its educational significance, the views of scholars who have contributed to the art of makom, and explains them on a scientific basis.